A taxonomic revision of two genera, Pleurolobus and Sohmaea (Leguminosae) in Thailand and Indo-China - Saisorn, Witsanu; Chantaranothai, Pranom (Phytotaxa, 2022)
There are two species of Pleurolobus and five species of Sohmaea in Thailand and Indo-China. Pleurolobus flexuosus and Sohmaea laxiflora are newly recorded for Cambodia. Taxonomic information of all species is provided. Lectotypes of six names, Desmodium cavaleriei, D. flexuosum, D. laxiflorum, D. macrophyllum, D. ormocarpoides var. velutina, and D. zonatum are designated. One new combination is made as Sohmaea laxiflora subsp. lacei.